Scaling-up climate services with users in Latin America - Navarro-Racines, Carlos Eduardo; Pons, Diego; Müller, Anna; González Romero, Carmen; Muñoz, Angel G; Giraldo Mendez, Diana Carolina; Martínez Barón, Deissy; Prager, Steven D.; Ramírez Villegas, Julián Armando (2020)
Latin America farmers are highly vulnerable to climate variability, with crop losses observed throughout the region on a virtually annual basis. For instance, as indicated by the United Nations’ Food and Agriculture Organization (FAO) and World Food Program (WFP), the 2014–2017 drought conditions in Central America affected over 3.5 million people in Guatemala, Honduras and El Salvador. At the same time, local stakeholders and farmers generally have limited access to existing climate and forecast information, do not have sufficient capacities to understand the climate information and/or mechanisms to relate this information to the impact that climate variations can generate at a local level. This precludes the translation of information into actionable knowledge, and therefore into action.